How Real is Too Real for the Law? Realism versus Right of Publicity in Video Game Design. Issue 3 (2nd July 2016) - Litty, Jamie M.
Abstract : Realistic elements in video game design can inspire an appropriation claim, trademark dispute, or similar lawsuits, even when the underlying immaterial property from the real world was licensed. Video games can be First Amendment-protected expression, however, as in other media, there's tension between the speech rights of creators and the personal rights of subjects. Furthermore, there's disagreement from one jurisdiction to another regarding how much mimicry loses protection and how many dissimilarities are transformative enough to be lawful. Analysis of case law reveals a balancing act between protecting video games as expressive works and protecting individuals' right of publicity.